KAJIAN POTENSI DAN DAYA DUKUNG TAMAN WISATA ALAM BUKIT KELAM UNTUK STRATEGI PENGEMBANGAN EKOWISATA - Sigit Purwanto; Lailan Syaufina; Andi Gunawan (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2014)
It is believed that ecotourism can increase community welfare and natural resource sustainability. Ecoutourism development in Bukit Kelam natural tourism park (TWABK) need to be based on the function and carrying capacity of the area, so that it must be discovered the object potential and tourism attraction. The study aimed to: (1) identify and analyze the object potential and natural tourism attraction in TWABK; (2) analyze carrying capacity of TWABK for ecotourism development, (3) identify and analyze the stakeholders of TWABK; and (4) formulate the strategies of ecotourism development in TWABK. Analysis guide of ADO-ODTWA Dirjen PHKA 2003 is used to analyze the object potential and natural tourism attraction. The criteria of Physical Carrying Capacity (PCC), Real Carrying Capacity (RCC) and Efective Carrying Capacity (ECC) is used to analyze the carrying capacity of TWABK. Stakeholder Grid is used to analyze the stakeholders and the ecotourism development strategies of TWABK which formulated by using SWOT analysis. Some objects in TWABK are feasible for ecotourism development, which are: bukit Kelam landscape, Kelam ring road, climbing transect, the hill peak, the foothills area, the hillside, spiritual tourism of Maria cave and agro tourism. The ECC of TWABK area for ecoutourism is 196 persons/day, with slope correction factor, soil erosion sensitivity, landsape potential, climate and wildlife disturbance (swallow birds spawn season). The stakeholders of TWABK is divided into four categories, which are: the key players (the ministry of forestry, the ministry of tourism and creative economy, the agency of cultural and tourism of Sintang district, the agency of forestry and plantation of Sintang district and the community),the context setters (the NGOs), the crowd (private sectors) and the subjects (visitors, academics, and refill drinking water company). The ecotourism development strategy formulation of TWABK results 9 strategies, which are: area stabilization, management plan formulation, ecotourism development according to the potency and carrying capacity of the area, publication and promotion, protection of the area, management collaboration, environmental education and counseling, community development,and ecotourism impacts monitoring and evaluation. Keywords: carrying capacity, ecotourism, strategy